A Comparative Analysis of Real and Predicted Inflation Convergence in Cee Countries During the Economic Crisis - Mihaela Simionescu (CES Working Papers, 2014)
The main objective of this study is to make a comparative analysis of inflation convergence in Central-Eastern European countries (CEE countries) during the economic crisis over 2008-2013. For Bulgaria, Czech Republic, Hungary, Poland, Romania and Slovakia the inflation convergence has decreased in the analyzed period, the coefficient of variation (64.22%) showing strong divergence compared to the slow divergence indirectly predicted by the European Commission. The negative catch-up rates for Bulgaria, Poland and Slovakia explain the large negative consequences of the actual economic crisis for these countries. The Fisher-type test for panel data indicated no convergence for real and predicted inflation convergence. The analysis based on random effects models indicated an inflation convergence rate of 15.47% in CEE economies compared to a predicted convergence rate of 2.04%.
Keywords: C53; E37; E52; 330; convergence; forecasts; accuracy; catch-up rate; panel unit root test Romania